Stereogram generation : concepts and implementation - Gupta, Tanvi Digmanu (2014)
Three – dimensional viewing has been a fascinating subject for many years. Early years comprised of assisted stereoscopic viewing through the use of devices like the stereoscope which employed two separate images to enable the viewing of the scene as a single three – dimensional image. Modern days have seen the advent of three – dimensional movies which make the scene look very realistic but still necessitate the use of special glasses for perceiving a sense of depth.